PEDAGOGIKALÍQ IZERTLEWLERDE BILIM ALÍWDÍŃ JAŃA KONCEPCIYASÍ - Allaniyazov, Ismail Begjanovich; Ismailov, Nurmukhammed Ziynatdin ulı (SCIENCE and SOCIETY, 2026)
The article is devoted to the modern doctrine of independent learning, which received the name "hytagogy" (euthagogy), the definition of this term, etymology and translation variants, and the comparative content of the terms pedagogy, andragogy, and hytagogy are presented.